Superior efficacy of midostaurin over cladribine in advanced systemic mastocytosis: a registry-based analysis : original reports - Lübke, Johannes; Schwaab, Juliana; Naumann, Nicole; Horny, Hans-Peter; Weiß, Christel; Metzgeroth, Georgia; Kreil, Sebastian; Cross, Nicholas C.P.; Sotlar, Karl; Fabarius, Alice; Hofmann, Wolf-Karsten; Valent, Peter; et al. (Journal of clinical oncology, 2022)
Purpose - On the basis of data from the German Registry on Disorders of Eosinophils and Mast Cells, we compared the efficacy of midostaurin and cladribine in patients with advanced systemic mastocytosis (AdvSM). - Patients and Methods - Patients with AdvSM (n = 139) were treated with midostaurin only (n = 63, 45%), cladribine only (n = 23, 17%), or sequentially (midostaurin-cladribine, n = 30, 57%; cladribine-midostaurin, n = 23, 43%). Prognosis was assessed through the Mutation-Adjusted Risk Score (MARS). Besides the comparison of efficacy between midostaurin and cladribine on response (eg, organ dysfunction, bone marrow mast cell [MC] infiltration, and tryptase), overall survival (OS), and leukemia-free survival, we focused on the impact of treatment on involved non-MC lineages, for example, monocytes or eosinophils, and the KIT D816V expressed allele burden. - Results - Midostaurin only was superior to cladribine only with effects from responses on MC and non-MC lineages conferring on a significantly improved OS (median 4.2 v 1.9 years, P = .033) and leukemia-free survival (2.7 v 1.3 years, P = .044) on the basis of a propensity score-weighted analysis of parameters included in MARS. Midostaurin compensated the inferior efficacy of cladribine in first- and second-line treatment. On midostaurin in any line, response of eosinophilia did not improve its baseline adverse prognostic impact, whereas response of monocytosis proved to be a positive on-treatment parameter. Multivariable analysis allowed to establish three risk categories (low/intermediate/high) through the combination of MARS and the reduction of the KIT D816V expressed allele burden of ≥ 25% at month 6 (median OS not reached v 3.0 years v 1.0 year; P < .001). - Conclusion - In this registry-based analysis, midostaurin revealed superior efficacy over cladribine in patients with AdvSM. In midostaurin-treated patients, the combination of baseline MARS and molecular response provided a compelling three-tier risk categorization (MARSv2.0) for OS.